EARLY CHILDHOOD ADVERSITY AND RECENT STRESS AFFECT RISK FOR DEPRESSIVE SYMPTOMS IN OLDER ADULTS. (11th November 2018) - Arpawong, T; Lee, J; Phillips, D; Prescott, C
Abstract: The stress sensitization hypothesis (SSH) postulates that the psychological impact of stressful life events (SLEs) is greater for adults with childhood trauma than those without. Most prior research evaluating the SSH and depressive symptoms (DepSx) is based on younger adults in cross-sectional studies, which cannot rule out alternative explanations, including reporting bias (i.e., DepSx cause higher endorsement of SLEs). We address these limitations in a longitudinal study of a U.S. population-representative sample of adults aged 50 and older using "objective" SLEs, unlikely to be influenced by DepSx. Childhood adversity was collected from 12, 119 participants in the U.S. Health and Retirement Study (60% female; age mean=58). Current DepSx, assessed by a modified CES-D, and recent SLEs were obtained in biannual interviews conducted in 1994–2010, yielding 83, 633 observations. Results from multi-level logit random effects models found individuals reporting early childhood adversity had much higher odds for DepSx, with a trend of declining strength of effect with increasing age. Odds for DepSx were higher in periods with recent SLEs than in periods without SLEs, with a stable effect through older age. Despite that higher depressive symptoms were independently associated with childhood trauma and recent stress, there was little evidence for the SSH; thus, childhood trauma did not amplify the effect of recent stress. In contrast to prior research, this lack of support found for the SSH is likely due to the sample age and greater methodological controls in this study.